TO SAYS THE STATUS OF AN ARTICLE, AND TO SAY AN ARTICLE IS THE STANDING - Ahmad Ghufron (Spektra: Jurnal Ilmu-ilmu Sosial, 2021)
Wisdom in the world of da'wah has a very important position, which can determine the success or failure of da'wah. As a da'wah method, wisdom is etymologically defined to refer to meanings such as justice, knowledge, wisdom, prophethood and also the Koran. And in terms of terminology, wisdom refers to the understanding of the accuracy of saying and acting and treating things wisely (al-ishabat fi al-aqwal wa al-af'al wadha'a kulla syay' fi maudhi'ihi). Yusuf Qardhawi in his book Fiqh Priority writes that many of his worries are related to the priority of charity which is not properly implemented by Muslims in social life, family, entertainment and others. He stated, “I saw some young people who were diligent in worship, but they treated their fathers, mothers and brothers harshly and harshly. Under the pretext that they are all perpetrators of disobedience or deviate from religious teachings. The youths have forgotten that Allah SWT. bequeath us to be good to both parents even though both of our parents are musicians and try to make us mushreek